2012
DOI: 10.1021/jm2009088
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationship Study of Antimicrotubule Agents Phenylahistin Derivatives with a Didehydropiperazine-2,5-dione Structure

Abstract: Plinabulin (11, NPI-2358) is a potent microtubule-targeting agent derived from the natural diketopiperazine "phenylahistin" (1) with a colchicine-like tubulin depolymerization activity. Compound 11 was recently developed as VDA and is now under phase II clinical trials as an anticancer drug. To develop more potent antimicrotubule and cytotoxic derivatives based on the didehydro-DKP skeleton, we performed further modification on the tert-butyl or phenyl groups of 11, and evaluated their cytotoxic and tubulin-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 56 publications
1
66
0
Order By: Relevance
“…The diketopiperazines inhibited the cell cycle at the G2/M phase by inhibiting tubulin polymerization. 15 Its tert-butyl derivative, named plinabulin 16 was entered into a phase III clinical trial for the treatment of advanced metastatic non-small cell lung cancer in 2015. 17 Isomethoxyneihumicin has a diketopiperazinelike core skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diketopiperazines inhibited the cell cycle at the G2/M phase by inhibiting tubulin polymerization. 15 Its tert-butyl derivative, named plinabulin 16 was entered into a phase III clinical trial for the treatment of advanced metastatic non-small cell lung cancer in 2015. 17 Isomethoxyneihumicin has a diketopiperazinelike core skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…This biological characteristic appeared to be similar to those of halimide 13 and plinabulin. 16 Unfortunately, the compound showed no activity against HCT116 cells, HaCaT cells or CHO cells, at least Isomethoxyneihumicin is a mixture of lactam-lactim tautomers 1 and 2 at a ratio of 2:1 in DMSO-d 6 . Although methoxyneihumicin (3) was previously reported to form a single structure, we found that it is also a mixture of lactam-lactim tautomers at a ratio of 5:1 in DMSO-d 6 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…51 Structureeactivity studies have shown that the potency of 23 can be further increased by attaching fluoro or benzoyl groups to the phenyl moiety. 52 Several DTrp-containing natural products have been discovered, but in light of the recent review in this area 2d only selected examples with interesting structures and/or potent bioactivity will be discussed herein. In 1958, Misiek et al isolated telomycin (24, Fig.…”
Section: Trisubstituted Ab-dehydroamino Acidsmentioning
confidence: 99%
“…19,20) We first established a convenient synthetic route to compound 7 that would allow for the synthesis of a variety of derivatives. Compound 7 was synthesized from pivalic anhydride 8a in six steps (Chart 1).…”
Section: Synthetic Route Of Plinabulin and Its Derivativesmentioning
confidence: 99%
“…Plinabulin (7) exhibited potent antitumor activity 19) and an interesting binding mode [36][37][38] ; however, its low water solubility (<0.1 µg/mL) needed to be improved to increase its pharmaceutical value. Compound 7 is currently injected in combination with a solubilizing agent that can induce hypersensitivity in the context of long-term administration.…”
Section: Development Of a Water-soluble Prodrug Of Plinabulinmentioning
confidence: 99%